2017
DOI: 10.1038/s41598-017-08555-0
|View full text |Cite
|
Sign up to set email alerts
|

Atomic Force Microscopy Reveals the Dynamic Morphology of Fenestrations in Live Liver Sinusoidal Endothelial Cells

Abstract: Here, we report an atomic force microscopy (AFM)-based imaging method for resolving the fine nanostructures (e.g., fenestrations) in the membranes of live primary murine liver sinusoidal endothelial cells (LSECs). From data on topographical and nanomechanical properties of the selected cell areas collected within 1 min, we traced the dynamic rearrangement of the cell actin cytoskeleton connected with the formation or closing of cell fenestrations, both in non-stimulated LSECs as well as in response to cytochal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
55
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(58 citation statements)
references
References 30 publications
(32 reference statements)
3
55
0
Order By: Relevance
“…Initially, the FFCs in a variety of forms (floating, flattening, spiraling) were identified using electron microscopy . In our previous work using QI AFM, we demonstrated that after application of cytochalasin B, a compound that disturbs actin polymerization, expansion of newly formed sieve plates occurred in the direction of FFC migration. The application of jasplakinolide, an actin‐modulating agent promoting actin polymerization, resulted in the appearance of many discrete islands of nonfenestrated areas within the sieve plates of live LSECs.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Initially, the FFCs in a variety of forms (floating, flattening, spiraling) were identified using electron microscopy . In our previous work using QI AFM, we demonstrated that after application of cytochalasin B, a compound that disturbs actin polymerization, expansion of newly formed sieve plates occurred in the direction of FFC migration. The application of jasplakinolide, an actin‐modulating agent promoting actin polymerization, resulted in the appearance of many discrete islands of nonfenestrated areas within the sieve plates of live LSECs.…”
Section: Resultsmentioning
confidence: 99%
“…Unless otherwise stated, LSECs were measured in 25 mM HEPES buffered medium. All images were acquired in force versus distance (FD)–based imaging mode (QI; JPK Instruments) according to a method described elsewhere . In brief, a single FD curve is performed in every pixel point of the image and then translated into images of topography and stiffness.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations